2021
DOI: 10.1088/1755-1315/818/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

First finding of spirurid larva (Chromadorea, Spirurida) in the common European viper Vipera berus (Linnaeus, 1758) of the Russian fauna

Abstract: The National park “Smolny” (Republic of Mordovia, Russia) is located in the Basin of Alatyr River, a second-order tributary of the Volga River. Favorable conditions are created for the development of helminths and infecting reptiles with them in floodplain biotopes. In 2018–2020 in this Protected Area we examined 25 individuals of the common viper Vipera berus (Linnaeus, 1758) by the method of complete helminthological dissection. We studied only road-killed vipers and reptiles killed by local residents. In to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…This study represents the rst molecular evidence of P. clausa in Iran. This parasite recognized as the type species of the genus, commonly parasitizes hedgehogs [15,25].In previous studies, this genus from the Physalopteridae family has been reported from three species of hedgehogs including E. europaeus, E. concolor, and H. auritus in Iran (Table 1). However, these reports were conducted only based on morphological features.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This study represents the rst molecular evidence of P. clausa in Iran. This parasite recognized as the type species of the genus, commonly parasitizes hedgehogs [15,25].In previous studies, this genus from the Physalopteridae family has been reported from three species of hedgehogs including E. europaeus, E. concolor, and H. auritus in Iran (Table 1). However, these reports were conducted only based on morphological features.…”
Section: Discussionmentioning
confidence: 94%
“…The heteroxenic life cycle of these nematodes is composed of insects (e.g. beetles or roaches) as an intermediate hosts and occasionally snakes, lizards, and anurans as paratenic hosts [12][13][14][15]. The infective larval stage (L3) is transmitted to de nitive hosts via ingestion of the infected intermediate or paratenic hosts [13].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise in other reptile hosts, helminth infection in vipers can be strongly in uenced by the selection of microhabitats and the prey items they consume (Brito et al 2014). For example, those snake species living in dry habitats and feeding on rodents are weakly infested by helminths (Kirillov and Kirillova 2021). Although the factors found here as predictors of helminth occurrence are not the same as those related to the consumption of major prey types in this viper species (Espasandín et al 2022), they align with the aforementioned pattern in V. seoanei.…”
Section: Biological and Eco-geographic Factors Related To Helminth Oc...mentioning
confidence: 99%
“…Some general characteristics of these larvae include a length of approximately 4.0 mm, pseudo-labia (5 mm) anterior to the oral opening, and an esophagus one third the length of the body. Two distinct characters include: a thick-walled cylindrical buccal capsule (36 mm) resembling the buccal cavity of habronematids, and a short, blunt tail, possessing a terminal spherical knob with minute tubercles, like that of Physocephalus sexalatus (Molin) larvae as described and illustrated by Kirillov and Kirillova (2021). The habitat of pus-filled cysts may indicate that P. guttatus is a paratenic host for this nematode.…”
mentioning
confidence: 98%
“…Goldberg and Bursey (2001) suggested that such larvae are likely temporary residents associated with inclusion of insects in a snake's diet. Kirillov and Kirillova (2021) reported and illustrated physalopterid larvae collected from salvaged Vipera berus (common European viper) specimens from Mordovia, Russia.…”
mentioning
confidence: 99%